Financing and commercialization of family farming in Gran La Plata. Study as part of a Territorial Development project - Cieza, Ramón I. (Centro de Historia Argentina y Americana, 2012)
Currently, family farming has taken visibility both in academic works and in the design of public policies. Even though are recognized own characteristics which differentiate it from the business production, they are presented according to the type of production and the territory where they are inserted, particularities that allow defining and analyzing them. In the case of family horticultural and flower production, which supplies with fresh products to big urban centers, the specificity of labor-intensive production system, the technologies utilized, the characteristics of the obtained products, their commercialization and their localization, differs substantially from others productive systems of the country. According to diagnosis made by INTA [2004] and other qualitative works in suburbs of Buenos Aires, the difficulties faced by these households are multiples. Among the most important are mentioned the subordination in the commercial chain and the access to financing. This paper seeks account for a territorial development project in the peri-urban region of Gran La Plata, which addresses from an integral perspective, to financing aspects and commercialization to family farmers It focuses on 30 family farmers from La Plata and Berazategui belonging to the project "Banco Social", implemented by Facultad de Ciencias Agrarias y Forestales from UNLP; advancing on an analysis regarding the access to financing and the commercial strategies carried out by the family farmers under study